Taraxasterol Acetate From Taraxacum officinale Ameliorates Dextran Sulfate Sodium–Induced Ulcerative Colitis in Mice in Association With Changes of the Metabolism and Structure of Gut Microbiota - Li Jin; Man Li; Beihui He; Liqin Li; Yingchao Liu; Jizhou Zhang; Biao Wang; Chengtao Sun; Guoyin Kai (Food Frontiers)
ABSTRACT Ulcerative colitis (UC) is closely associated with the structural and metabolic disorders of gut microbiota. Taraxasterol acetate (TSA) from Taraxacum officinale (TO) has anti‐inflammatory activity. In this study, to investigate the therapeutic potential of TSA and its mechanism of action in dextran sulfate sodium (DSS)‐induced UC. The anti‐inflammatory effects of TSA were evaluated in vitro. DSS‐induced UC animal models and TSA gavage were employed for in vivo experiments. The results indicated that TSA showed good anti‐inflammatory effects both in vitro and in vivo, and the anti‐UC effect of TSA was better than that of the extract in vivo. TSA relieved clinical symptoms in DSS‐induced UC mice and repaired the intestinal barrier. TSA restored the structural disorder of gut microbiota and regulated metabolic levels in DSS‐induced UC mice. This study provides a fresh perspective on developing new therapeutic methods against UC using the traditional Chinese medicine TSA.